Avances en los estudios económicos sobre recursos naturales en el Perú durante el periodo 2016-2021 - Orihuela, Carlos (2022)
This review contains several economic investigations on natural resources from 2016-2021. Most of these researchers relate this research biodiversity and ecosystem services. In the latter case, most of it comes from a thesis. A lot of studies come from public universities, which is an encouraging detail; however, less than half of such studies have managed to be published in a scientific journal. These results show the growing interest of academics in several topics, such as the environmental management of natural resources.